PENGARUH INSEKTISIDA NABATI KAMANDRAH DAN AKAR TUBA TERHADAP WERENG BATANG COKLAT - Agus Kardinan; Molide Rizal; Paramita Maris (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[THE INFLUENCE OF BOTANICAL INSECTICIDES BASED ON CROTON OIL AND DERRIS ROOT AGAINST BROWN PLANTHOPPER]. Brown planthopper (BPH) (Nilaparvata lugens Stall) is a serious pest in rice. Using synthetic insecticide to control BPH is harmful for human health and can caused environmental pollution. The objective of this research is to find out ecofriendly insecticide to control BPH. Research has been conducted at Entomological laboratory, Indonesian Spice and Medicinal Crops Research Institute (ISMECRI), Bogor. It was designed with CRD, 16 treatments and 3 replications. Treatments consisted of botanical insecticides based on Croton tiglium and Derris elliptica. Each material was extracted by water, methanol, and xylene, and then tested by individually and combination, so there were 15 formulas and 1 control treatment (water). Third nymph BPH and IR64 rice variety were used in this research. Research was done in two methods, i.e. contact application and residual application. The result shows that there are 11 formulas which are prospective to be further developed i.e aqueous extraction (6 formulas) and combination extraction (aqueous with xylene and methanol (5 formulas). The aqueous extraction maybe the most prospective formulation since the technique could easily be adopted by farmers. Botanical pesticide based on Croton tiglium and Derris elliptica are very promising, therefore the research should be continued to find out the best formula of botanical insecticides for controlling BPH).